2022
DOI: 10.3389/fpubh.2022.868822
|View full text |Cite
|
Sign up to set email alerts
|

Applying Existing Particle Paradigms to Inhaled Microplastic Particles

Abstract: Ambient particulate pollution originating from plastic contaminates air, including indoor and urban environments. The recent discovery of ambient microplastic (MP) particles of a size capable of depositing in the thoracic region of the airway, if inhaled, has raised concern for public exposure and health impacts following lessons learned from other particle domains. Current microplastic exposure estimates are relatively low compared to total ambient particulate matter, but optimal analytical techniques and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In the field of public health research, the study of MNPs exposure pathways is more diverse, in that, in addition to the oral exposure pathways such as eating food and drinking water, a considerable number of studies have been conducted on atmospheric MNPs concentration levels and respiratory exposure pathways [ 15 , 16 ]. In terms of abundances, MNPs in the atmosphere can reach up to four orders of magnitude higher in indoor and urban environments, far exceeding the levels at which they have been detected in the same volume of aqueous sediments and organisms [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of public health research, the study of MNPs exposure pathways is more diverse, in that, in addition to the oral exposure pathways such as eating food and drinking water, a considerable number of studies have been conducted on atmospheric MNPs concentration levels and respiratory exposure pathways [ 15 , 16 ]. In terms of abundances, MNPs in the atmosphere can reach up to four orders of magnitude higher in indoor and urban environments, far exceeding the levels at which they have been detected in the same volume of aqueous sediments and organisms [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence demonstrates the presence of MPs in both outdoor and indoor air, and fibers have been detected in marine ecosystems and aquatic organisms. Consequently, the inhalation of MPs poses a potential risk to human health, particularly in young children who frequently engage in hand-to-mouth behaviors [8,14].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Recent evidence shows that ambient MP particles, when inhaled, are capable of depositing in the human airway. 2 , 3 , 4 Following lessons learned from other particles, there have been concerns about the possible health impact of this exposition. 4 , 5 In fact, it has been shown that MPs induce chronic inflammation and DNA damage and oxidative stress, leading to carcinogenesis.…”
mentioning
confidence: 99%
“… 2 , 3 , 4 Following lessons learned from other particles, there have been concerns about the possible health impact of this exposition. 4 , 5 In fact, it has been shown that MPs induce chronic inflammation and DNA damage and oxidative stress, leading to carcinogenesis. 6 Studies in humans have demonstrated that these products are more frequently detected in patients with worse pulmonary function and in lung cancer tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation